EFFECT OF NEEM LEAVES EXTRACT AND ORGANIC FERTILIZER IN THE PRODUCTIVITY AND QUALITY OF TWO POTATO CULTIVARS - & Hussein, Shayaa (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This research was conducted at the fields of College of Agriculture, University of Baghdad during spring  and fall seasons 2017 to study the effect of addition methods of Neem leaves extract and organic fertilizer in the productivity and quality of two potatoes cultivars. The experiment was carried out using split plot arrangement within Randomized Complete Block Design, with three replicates. The experiment included two Potato cultivars ,Burren (V1) and Riviera(V2) as the main factors and nutritional treatments as follow: control treatment T1, Recommend fertilizer T2, cows manure 5% of soil weight T3, irrigation with cows manure  T4, cows manure 5%of soil weight+recommend chemical fertilizer T5, Spraying the Neem leaves extract with a concentration of (2.5 g L-1)+cows manure 5% T6, Spraying the Neem leaves extract with a concentration of (5g L-1)+cows manure 5% T7, Spraying the Neem leaves extract with a concentration of (7.5 g L-1) + cows manure 5% T8,  irrigation with Neem leaves extract with 25% concentration +cows manure 5% T9, irrigation with Neem leaves extract with 50% concentration+ cows manure 5% T10,  irrigation with Neem leaves extract with 75% concentration of concentrated solution for Neem leaves extract+cows manure 5% T11 and irrigation with Neem leaves extract with 100% concentration+cows manure 5% T12.as sub plots, T8 treatment was significantly superior in the total yield, compared with the lowest average of total yield in control treatment T1, The V1 produced a significantly highest total yield and the marketable yield for plant compared to V2 for two seasons, The T8V1 interaction treatment was significantly superiority  in the increase of total yield compared to the lowest average for T1V2 treatment, the response of two potato cultivars  differed to the nutrition treatments.